HUBUNGAN ANTARA TINGKAT KREATIVITAS VERBAL DENGAN KEMAMPUAN BERBAHASA INGGRIS PADA MAHASISWA JURUSAN PSIKOLOGI ISLAM IAIN PONTIANAK ANGKATAN 2017/2018 - Isyatul Mardiati Mardiati (Universitas Negeri Makassar, 2020)
Abstract This study described about: (1) the level of verbal creativity of students of the Islamic Psychology Ushuluddin, Adab and Da’wah Faculty, Islamic State Institute of Pontianak 2017/2018; (2) English language proficiency of students of the Islamic Psychology Ushuluddin, Adab and Da’wah Faculty, Islamic State Institute of Pontianak 2017/2018; (3) the relationship between the level of verbal creativity and English language proficiency of students of the Islamic Psychology Ushuluddin, Adab and Da’wah Faculty, Islamic State Institute of Pontianak 2017/2018. The sample in this study were students of the Department of Islamic Psychology, Faculty of Ushuluddin, Adab and Da'wah, Islamic State Institute of Pontianak. The results of this study are that there is a positive correlation between verbal creativity with English language proficiency in Islamic Psychology students From this research, it can also be seen that the level of verbal creativity of Islamic Psychology students is quite high with a percentage of 49.2% and English proficiency of students has a high category in reading skills. Keywords: Verbal Creativity, English Proficiency